Shock-produced high-pressure (La, Ce, Th)PO4 polymorph revealed by microstructural phase heritage of monazite - Erickson, Timmons; Timms, Nick; Pearce, M.A.; Cayron, C.; Deutsch, A.; Keller, L.P.; Kring, D.A. (GEOLOGICAL SOC AMER, INC, 2019)
The responses of uranium-bearing accessory minerals to shock metamorphism have received growing interest, because under extreme pressure and temperature conditions, these phases can form unique microstructures and/or polymorphs and their radiometric ages can be partially to wholly reset. This study presents new, high-resolution electron backscatter diffraction microstructural analyses of shock-deformed monazite, (La, Ce, Th)PO4, from the Haughton Dome, Nunavut, Canada, and the Nördlinger-Ries Crater, southern Germany. At each locality, shocked monazite grains contain distinctive lamellae comprising interlocking laths in four systematic crystallographic orientations. Modelling of orientation relationships among these lath-textured microstructures reveals that they were produced by reversion from lamellae of a previously undescribed high-pressure polymorph with a tetragonal symmetry. This is the first report of polymorphism found in natural (La, Ce, Th)PO4. The orientation relationships, lamellar forms, and ready reversion to monazite at low pressures are consistent with a deviatoric transformation. The former presence of this new (La, Ce, Th)PO4 polymorph is detected in moderately to highly shocked rocks, suggesting that it may be common at other impact craters.